Dua Mazhab Emanasi dalam Filsafat Islam Klasik dan Implikasi Teologisnya - Ali, Ibnu (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2016)
Islamic philosophy, which has been an accumulation of relation between pure logic and religious texts (naql), has a uniquely different features from the philosophy of Aristotle. This is because the Islamic philosophy has met not only with the pre-Islamic sciences but it also has thoroughly interacted with various branches of the Islamic knowledge such as theology, taá¹£awwuf, uá¹£Ã»l al-fiqh, and tÃ¢rÃ®kh al-tashrÃ®Ê». The interaction has resulted in numerous different thoughts within the Islamic philosophy itself as can be identified among the peripatetic Islamic philosophers. The article is intended to describe that in discussing cosmological matter, the majority of these philosophers put emphasis on Plotinusâs concept of emanation. However, the concept has led to distinctively diverse schools of philosophy in Islam. The study finds that the philoso-phers with strong background of scientific disciplines produced considerably different thought of emanation from those with strong background of Islamic knowledge. The first school consists of scientists-philosophers affiliated to the thought of Pythagoras, Plato, and Aristotle though with new concepts they proposed. The second school comprises Sufi-philosophers whose concepts have been strongly influenced by intuition though there have been conceptual differences based on their spiritual experiences.